Morphological variation of the rare psammophilous species Apostolepis gaboi (Serpentes, Dipsadidae, Elapomorphini) - Guedes, Thaís B.; Barbo, Fausto E.; França, Daniella; Zaher, Hussam (Zootaxa, 2018)
Apostolepis gaboi was described based only on the holotype found in the Queimadas, state of Bahia, northeastern Brazil. Since its original description, no additional specimens were reported in literature and the species was considered to be rare and poorly known. Here, we provide a detailed description for the species based on the examination of the holotype and 34 additional specimens from the type locality and adjacent areas. Additional information is also provided on intraspecific color variation and hemipenial morphology.